Nucleic acid changes during photodynamic inactivation of bacteria by cationic porphyrins - Alves, Eliana (2019)
Light activation of photosensitizing dyes in presence of molecular oxygen generates highly cytotoxic reactive oxygen species leading to cell inactivation. Nucleic acids are molecular targets of this photodynamic action but not considered the main cause of cell death. The in vivo effect of the photodynamic process on the intracellular nucleic acid content of Escherichia coli and Staphylococcus warneri was evaluated herein. Two cationic porphyrins (Tetra-Py+-Me and Tri-Py+-Me-PF) were used to photoinactivate E. coli (5.0 μM; 108cells mL-1) and S. warneri (0.5 μM; 108cells mL-1) upon white light irradiation at 4.0 mW cm-2for 270 min and 40 min, respectively. Total nucleic acids were extracted from photosensitized bacteria after different times of irradiation and analyzed by agarose gel electrophoresis. The double-stranded DNA was quantified by fluorimetry and the porphyrin binding to bacteria was determined by spectrofluorimetry. E. coli was completely photoinactivated with both porphyrins (5.0 μM), whereas S. warneri was only completely inactivated by Tri-Py+-Me-PF (0.5 μM). The hierarchy of nucleic acid changes in E. coli was in the order: 23S rRNA > 16S rRNA > genomic DNA. The nucleic acids of S. warneri were extensively reduced after 5 min with Tri-Py+-Me-PF but almost unchanged with Tetra-Py+-Me after 40 min of irradiation. The amount of Tri-Py+-Me-PF bound to E. coli after washing the cells is higher than Tetra-Py+-Me and the opposite was observed for S. warneri. The binding capacity of the photosensitizers is not directly related to the PDI efficiency or nucleic acid reduction and this reduction occurs in parallel with the decrease of surviving cells.